Percepções de discentes, usuários e profissionais de saúde sobre a integração Ensino – Serviço – Comunidade: um relato de experiência na cirurgia ambulatorial da Universidade Federal de São João Del-Rei no município de Tiradentes - Mello, Ludmila Leite Sant’Anna Vaz de (2020)
Introduction: National Curriculum Guidelines (DCN in Brazilian Portuguese) for Medical School in Brazil (BRASIL, 2014a) focus on essential healthcare, with a main curricular axis developing from the population’s health needs, integrating education, health, and community, preferably using the unified public health system known as SUS in Brazil. Considering such aspects, basic health network is a privileged teaching and learning scenery, as students experience health policies arranging their practice, especially in multiskilled teams. Furthermore, students can hence face real issues, connecting their learning work experience within their academic medical education to social health needs, focusing on public health (BRASIL, 2014a). Aims: To analyze work-learning integration features contributing to the university, as well as the community and their health issues, hardships, and challenges health users, students, and professionals observe in ambulatory surgery and the University (UFSJ) projects for the community in health units in the city of Tiradentes, in the state of Minas Gerais, southeastern Brazil. Methods: Qualitative study using data from semistructured interviews with health users, professionals, and students concerning their perception of integrating educational community service (IESC in Brazilian Portuguese). The research employed the content analysis technique to analyze data. Results and discussion: IESC helped improve work quality during service while qualifying professionals. In addition, it brought about self-realization to those therein interacting. It also brought about improvements to primary healthcare, enabling those involved to better comprehend the process toward greater solvability in the basic unit. Another aspect standing out in the research concerned challenges and halting hazards in this integration yet to be overcome, such as the lack of structure and materials, minority discomfort, and, last but not least importantly, concerning patients students attended to while facing the work routine of local health professionals with the university. Conclusion: The University inserted in the social reality, providing primary care services, help to better enable professionals to deal with more prevalent common issues, familiarizing them with public health principles, to the benefit of the population and local health teams, improving healthcare and solvability toward local community satisfaction